PENERAPAN (ROM) PASIF PADA LANSIA DENGAN GANGUAN MOBILITAS FISIK DI PANTI GRIYA JANATI - Hamna Vonny Lasanuddin; Sri Yulian Hunowu; Moh. Yusran Basri (Institut Nalanda, 2023)
Introduction: Stroke is a major health problem for today's modern society. Today, stroke is becoming a serious problem worldwide. This is because a sudden stroke can result in death, physical and mental disability in productive and old age. Methods: This study used a qualitative approach with the case method. Sunberg (2007) explains that a case study is a report or narrative by a therapist about the treatment of a single client, even though the report could be about a family or a group. In addition, this study also uses